THE IMPORTANCE OF WORKING IN GROUPS IN TEACHING (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article you will be given information about working in groups and its benefits. Mainly, you will response questions, what is team working? Moreover, there can be the number of ways in order to improve team working? Finally, you will be acquired data about positive aspects and drawbacks of team working and the role of working in groups in companies.